The DESIGN OF A TRANSMISSION SYSTEM ON A BALL MILL MACHINE TO PROCESS HOMOGENIZATION OF BLACK POWDER USING AN AUTOMATIC SYSTEM - Muhammad Rofiq; Lalu Saefullah; Mohammad Ali (Jurnal Otoranpur, 2021)
Abstract: In the military world, battle technology has experienced very rapid development, both close-range combat and long-range combat. In long-distance combat the technology that is often used is rocket technology where this rocket technology can paralyze the enemy in large numbers. Black powder is a mixture of potassium nitrate (KNO3), carbon powder (C) and sulfur (S). (Evie Lestariana, LAPAN). The black powder itself functions as an igniter filling material for the propellant combustion process. This research is to design a tool to support the manufacture of black powder in the igniter filling to help the combustion of rockets, especially those owned by the Indonesian Army. This study uses an experimental method using empirical calculations to get a tool with the desired specifications. Before carrying out the calculations, the author collects research data to carry out calculations, the data collected are as follows: 1. Roller shaft rotation: 246 rpm, 2. Roller shaft torque: 4.0697 Nm, 3. Roller shaft diameter: 25 mm, 4. Pulley shaft diameter top: 100mm. The results obtained after carrying out the calculations are the diameter of the driving pulley 98 mm, the belt contact angle against the pulley 174.6º, and the length of the V-belt 453.14 mm, moment of inertia on the gearbox output shaft 1884,8 mm4.